Army relations with Congress : thick armor, dull sword, slow horse - Scroggs, Stephen K., 1954- (Prager, 2000)
Relying on extensive candid interviews from members of Congress and staff on defense authorization committees and senior Army general officers, Scroggs provides a strong insider analysis with recommendations. He examines the impact of culture on the varying abilities of public agencies, specifically the Army, to pursue its organizational interests through lobbying or liaising Congress. Scroggs argues that despite structural similarities in how the four military services approach Congress, differences in service culture affect their relative success in achieving their goals on the Hill.